Категорія інформативності в сучасному британському пісенно-драматичному дискурсі - Бєляєва, Оксана Юріївна; Bieliayeva, O.Yu. (Харків : Харківський національний університет імені В.Н. Каразіна, 2020)
Bieliayeva O.Yu. Category of Information Value in Modern British Song and Dramatic Discourse. — Qualification scholarly paper: a manuscript. Dissertation for the Doctor of Philosophy degree in Humanities by speciality 035 — Philology. — V. N. Karazin Kharkiv National University, Ministry of Education and Science of Ukraine, Kharkiv, 2020. The dissertation deals with the study of Modern British song and dramatic discourse in the vocal and instrumental space of Great Britain. It is represented by the corpus of dramatic songs, concert performances, and video clips from thirty-two albums of the well-known British pop-groups THE RUBETTES, ABC, 5IVE, LUCKY SOUL, HURTS, LONDON GRAMMAR, YEARS AND YEARS.
Category of Information Value in Modern British Song and Dramatic Discourse
Дисертаційна робота присвячена вивченню сучасного британського пісенно-драматичного дискурсу у вокально-інструментальному просторі Великої Британії на матеріалі драматичних пісень, концертних виступів та відеокліпів із тридцяти двох альбомів поп-гуртів THE RUBETTES, ABC, 5IVE, LUCKY SOUL, HURTS, LONDON GRAMMAR та YEARS AND YEARS.
Keywords: діалогізм; драматизм; драматична пісня; інформативний модус; категорія інформативності; підвищена дискурсивність; пісенно-драматична інформема; пісенно-драматичний дискурс; пісенно-драматичний текст; оцінка; простір і час; подія; факт уяви; функціонально-комунікативна стилістика тексту; category of information value; dialogism; dramatic song; dramatism; estimation; event; fact of imagination; functional-communicative stylistics of text; increased discursiveness; informative modus; song and dramatic discourse; song and dramatic informeme; song and dramatic text; space and time